2022
DOI: 10.1523/jneurosci.1546-22.2022
|View full text |Cite
|
Sign up to set email alerts
|

The Spatiotemporal Neural Dynamics of Object Recognition for Natural Images and Line Drawings

Abstract: Drawings offer a simple and efficient way to communicate meaning. While line drawings capture only coarsely how objects look in reality, we still perceive them as resembling real-world objects. Previous work has shown that this perceived similarity is mirrored by shared neural representations for drawings and natural images, which suggests that similar mechanisms underlie the recognition of both. However, other work has proposed that representations of drawings and natural images become similar only after subs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…2b for a schematic). We chose to assess these shared alpha representations across the entire imagery period while maintaining temporal resolution for the perceptual data in order to increase the power of the analysis, since imagery representations were found to be relatively invariable across time (Corriveau et al, 2023; Dijkstra et al, 2018; Xie et al, 2020), whereas perceptual representations are thought to be more temporally variable (Carlson et al, 2011; Dijkstra et al, 2018; Singer et al, 2023). This yielded a time-resolved measure of shared representations in the alpha band between scene imagery and each stage in the processing hierarchy of scene perception, in which temporal representational variations index the procession of perceptual processing (King & Dehaene, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2b for a schematic). We chose to assess these shared alpha representations across the entire imagery period while maintaining temporal resolution for the perceptual data in order to increase the power of the analysis, since imagery representations were found to be relatively invariable across time (Corriveau et al, 2023; Dijkstra et al, 2018; Xie et al, 2020), whereas perceptual representations are thought to be more temporally variable (Carlson et al, 2011; Dijkstra et al, 2018; Singer et al, 2023). This yielded a time-resolved measure of shared representations in the alpha band between scene imagery and each stage in the processing hierarchy of scene perception, in which temporal representational variations index the procession of perceptual processing (King & Dehaene, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Shatek et al, 2019;Xie et al, 2020) and the multitaper approach typically increases the signal-to-noise ratio in frequency-resolved data at the expense of increased temporal and frequency smoothing (Cohen, 2014). In addition, we decided to omit temporal resolution of the frequency decomposition of the imagery data while maintaining it for the perception data in order to further boost power, since imagery representations have been shown to be relatively invariable across time (Corriveau et al, 2023;Dijkstra et al, 2018;Xie et al, 2020) while perceptual representations have been shown to be temporally variable as a function of the different processing stages in the visual hierarchy (Carlson et al, 2011;Dijkstra et al, 2018;King & Dehaene, 2014;Singer et al, 2023). Extracted frequencies ranged from 4-30 Hz, thus covering the theta (4-7 Hz), alpha (8-13 Hz) and beta (14-30 Hz) frequency bands.…”
Section: Frequency Decompositionmentioning
confidence: 99%
“…One theoretical question in the object recognition literature that this experiment cannot answer is: what do photographs truly add to recognition relative to line drawings (e.g., Biederman, 1987 ; Singer et al, 2023 ; Uttl et al, 2006 )? This is not a question that this study was designed to address as we did not directly compare Snodgrass and Vanderwart’s ( 1980 ) line drawings or Rossion and Pourtois’s ( 2004 ) textured drawings against our new greyscale and color photographic stimuli.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore the final sample consisted of 31 participants (mean age pm SD = 21.77 pm 3.31; 21 female). The number of participants was selected to match the average number of participants used in previous studies that employed MVPA analysis (Leonardelli et al, 2019; Dirani and Pylkkänen, 2023; Singer et al, 2023). The study was conducted at the Center of Human Brain Health in Birmingham, United Kingdom.…”
Section: Methodsmentioning
confidence: 99%